The relationship between hours of sleep, screen time and frequency of food and drink consumption in Spain in the 2011 and 2013 ALADINO: a cross-sectional study - Napoleón Pérez-Farinós; Carmen Villar-Villalba; Ana María López Sobaler; María Ángeles Dal Re Saavedra; Aránzazu Aparicio; Sara Santos Sanz; Teresa Robledo de Dios; José Javier Castrodeza-Sanz; Rosa María Ortega Anta (BMC, 2017)
Abstract Background The frequency of intake of food and beverages depends on a number of ill-defined behaviour patterns. The objectives of this study were to evaluate the effects of screen time and sleep duration on food consumption frequency, and to describe frequencies and types of food consumption according to BMI category and parents' level of education. Methods We studied 6287 and 2806 children drawn from the 2011 and 2013 cross-sectional ALADINO studies respectively. Data were collected on number of hours of sleep, screen time, and weekly frequency of consumption of 17 food groups. Weight status was measured, and information was also collected on parents' educational level. Average food consumption frequencies were calculated by reference to hours of sleep and hours of screen time, and were defined as ≥4 times or <4 times per week (once per week for soft drinks and diet soft drinks). Differences in frequency were evaluated for screen times of more and less than 2 h per day, and for sleep durations longer or shorter than the daily average. We fitted logistic regression models to evaluate the independent association between screen exposure and hours of sleep on the one hand, and food consumption frequency on the other. Results Consumption of fruit and vegetables was lower among children who had parents with no formal or only primary school education. High levels of screen time were associated with a greater frequency of consumption of energy-dense, micronutrient-poor products and a lower frequency of consumption of fruit and vegetables. Sleeping a sufficient number of hours was associated with a higher consumption of fruit and vegetables. The results for 2011 were concordant with those for 2013. Conclusions If efforts to ensure healthier eating habits among children are to be at all successful, they should focus on promoting a sufficient amount of sleep for children, limiting the time they spend watching television and/or playing with computers or video games, and educating parents accordingly.